Potential association of muscarinic receptor 3 gene variants with primary Sjögren's syndrome. Issue 7 (30th March 2011) - Appel, Silke; Le Hellard, Stephanie; Bruland, Ove; Brun, Johan G; Omdal, Roald; Kristjansdottir, Gudlaug; Theander, Elke; Nordmark, Gunnel; Kvarnström, Marika; Eriksson, Per; Rönnblom, Lars; Wahren-Herlenius, Marie; et al.
Abstract : Background: Primary Sjögren's syndrome (pSS) is characterised by a chronic inflammation of exocrine glands. Salivary gland infiltrates, however, do not correlate well with disease symptoms, and a primary role for the salivary gland parenchyma in disease development has been suggested. Specifically, dysfunction of exocrine pathways involving the muscarinic receptor 3 (CHRM3) has been indicated. Objective: To investigate possible genetic divergence in the CHRM3 gene in patients with pSS. Methods: 530 patients with pSS and 532 controls from a combined Swedish and Norwegian cohort were genotyped for 84 single nucleotide polymorphisms (SNPs) distributed throughout CHRM3 . Results: Genetic association was observed with five SNPs localised in intron 3 and 4 of CHRM3, the strongest being rs7548522 (minor allele frequency = 0.06, OR=1.93, 95% CI (1.24 to 3.01); p=0.0033). In addition, clinical parameters, including focus score, abnormal Schirmer's test and presence of autoantibodies, were associated with different SNPs in CHRM3 . Conclusion: The study demonstrates a novel association of CHRM3 polymorphisms with pSS, suggesting a functional role for CHRM3 and the salivary gland parenchyma in the pathogenesis of pSS.